Process engineering and development of post-combustion CO2 separation from fuels using limestone in CaO-looping cycle - Kavosh, Masoud (Cranfield University, 2011)
Global CO2 emissions produced by energy-related processes, mainly power plants, have increased rapidly in recent decades; and are widely accepted as the dominant contributor to the greenhouse gas (GHG) effect and consequent climate changes. Among countermeasures against the emissions, CO2 capture and storage (CCS) is receiving much attention. Capture of CO2 is the core step of CCS as it contributes around 75% of the overall cost, and may increase the production costs of electricity by over 50%. The reduction in capture costs is one of the most challenging issues in application of CCS to the energy industry. Using limestone in CaO-looping cycles is a promising capture technology to provide a cost-effective separation process to remove CO2 content from power plants operations. Limestone has the advantage of being relatively abundant and cheap, and that has already been widely used as a sorbent for sulphur capture. However, this technology suffers from a critical challenge caused by the decay in the sorbent capture capacity during cyclic carbonation/calcination, which results in the need for more sorbent make-up; hence a reduction in cost efficiency of the technology. The performance of sorbent influenced by several operating and reaction conditions. Therefore, much research involves investigation of influencing factors and different methods to reduce the sorbent deactivation. Cont/d.
Keywords: CO2 capture; CO2 separation; Carbon capture and storage; Limestone; CaO-looping cycle; Calcination-carbonation; Global warming; Climate changes; Greenhouse gas emissions; fossil fuels